Device malfunction caused by “auto-oversensing” of transthoracic impedance measurement test pulses in a modern minute ventilation dual-chamber pacemaker - Hansen, Claudius; Vollmann, Dirk; Neuzner, Jörg (Clinical research in cardiology, 2016)
Oversensing of physiologic and non-physiologic electrical signals is a relevant cause of malfunctions in subjects with CIED. Physicians taking care of CIED patients must be aware of the potential causes of oversensing and their pattern in EGMs. The present case describes an uncommon source and unique underlying root cause for oversensing in a modern dual-chamber MV rate-adaptive pacemaker.